26 Application and retention of evidence based practice skills: students and practitioner's perspectives from an indian healthcare institution. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Chandran, Viji; Thunga, Girish; Pai, Girish; Khan, Sohil
Abstract : Objectives: With two decades of introduction of Pharmacy Practice education and a decade of Pharm D program in India, there has been a paradigm shift in the practice of evidence-based clinical pharmacy/pharmacology in the country. Wide variation exists in the requirement of teaching evidence based medicine/evidence based practice (EBP) across health discipline in India. The Pharmacy Council of India lists 'provision of evidence-based pharmaceutical care' as one of the core duties for a registered pharmacy practitioner. With the efforts being on integrating clinical focused role of a pharmacist there is a need to contemplate where the EBP learning and teaching skills stands at this juncture. The present study aimed to identify and assess specifics knowledge gaps, attitudes and retention of EBP skills among pharmacy student cohort and to comment on their relation to current education practices. The study also aimed to assess practitioner's perspective on EBP skills at workplace. Method: A prospective cross-sectional study was undertaken as a component of need-analysis to identify and assess specific student perspective on EBP teaching and workforce preparedness. Institution ethics approval was obtained prior to the study. The study included feedback from students enrolled in Master in Pharmacy (M.Pharm) in Pharmacy Practice program and students enrolled in Pharm D program in year 5 and 6. Feedback from clinicians (registered medical practitioners and residents) were also obtained to perceive their understanding of need for EBP skilled graduates. Questionnaire were designed, piloted and standardised based on educational evidence and expert opinion. Descriptive statistics were applied to extract the key points from the need analysis. Results: A total of 40 students participated in the survey. Majority (95%) of the participants felt the need for training in core evidence-based skills (critical appraisal skills and knowledge of clinical epidemiology principles). Sixty five percent of the pharmacy interns reported lack of workforce preparedness to integrate EBP skills whilst provision of pharmaceutical care. Reported barriers include lack of training in the curriculum and demanding time at workplace. Students felt the need to reduce the mechanistic of EBP provision through integration of mobile application and periodic educational activities. Twenty-eight medical practitioners and 12 residents provided their feedback. Lack of training among the interns and students to facilitate EBP at workplace was highlighted. Need for innovative methods to reduce time-spent in critical appraisal of biomedical evidence was emphasised. This included concise, pre-appraised/synthesised source of evidence with easy accessibility at workplace. Conclusions: Current findings suggest that recent graduates are less than optimally equipped with the behaviour, knowledge and skills required for EBP at workplace. The curriculum needs consolidation of EBP component. Existing evidence tools/critical appraisal methods are not easily transferable in demanding workplace. With the ever-changing demands of healthcare workplace into which the students are transitioning, EBP teaching has a challenging task to meet student and employer need and provide better patient care in a country with diverse health issues and significant gaps in evidence-based clinical practice.